Cover Image, Volume 85, Issue 12. Issue 12 (6th November 2017) - McDougall, Matthew; Francisco, Olga; Harder‐Viddal, Candice; Roshko, Roy; Meier, Markus; Stetefeld, Jörg
Abstract : The cover image, by Matthew McDougall et al., is based on the Research Article Archaea S‐layer nanotube from a "black smoker" in complex with cyclo‐octasulfur (S8) rings, DOI:10.1002/prot.25385 .